Exploring the "Black Box" of Programming: Applying Systematic Implementation Evaluation to a Structured Camp Curriculum. (June 2015) - Mainieri, Tracy L.; Anderson, Denise M.
Camp scholars have designed structured curricula to engender specific outcomes and to break down the "black box" of programming. Implementation evaluation explores how well a program operates when delivered, further breaking down the black box. The purpose of this study was to explore the implementation of a new structured camp curriculum. The unit of analysis was a pilot camp program, Teens Leading & Connecting (TLC). Methods for this study included two direct observation tools and facilitator interviews. The findings suggest that TLC was implemented with quality and fidelity, and that a variety of mechanisms and contexts supported the implementation of TLC. Understanding these mechanisms and contexts can inform the implementation of TLC, and similar programs, in new camp environments. Furthermore, the results of this study demonstrate that implementation evaluation can inform program delivery in an intentional manner in camp and other youth-serving program contexts.